Cassirer et Panofsky : un malentendu philosophique - Mermet, Rémi (Labyrinth, 2020)
Cassirer and Panofsky: A Philosophical Misunderstanding This paper argues that German art historian and iconologist Erwin Panofsky unintentionally misused the concept of "symbolic form" coined by his friend and colleague, philosopher Ernst Cassirer. Although both shared the same neo-Kantian background, I contend that Panofsky clung to Kant’s dualistic theory of knowledge, while Cassirer explicitly adopted a non-dualistic way of thinking largely inspired by Goethean morphology. That is why Panofsky could distinguish between the "natural" space of perception and the cultural space of artistic representation, when Cassirer refused such a possibility. In so doing, Panofsky proved that he totally missed Cassirer’s point: according to the philosopher of symbolic forms, there is no such thing as a "nature," unless this "nature" is grasped as inherently cultural and historical.